1995
DOI: 10.1111/j.1365-2818.1995.tb03557.x
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of interlayers in different Nicalon fibre/glass matrix composites and their effect on mechanical properties

Abstract: Key words. Nicalon fibre-reinforced borosilicate glass, interlayer structure, transmission electron microscopy, in situ deformation. Summaryestablish the relationship between the structure of the Interlayer phenomena, revealed by high-voltage electron microscopy (HVEM) and high-resolution electron microscopy (HREM), are presented as they occur in various SiC(Nica1on) fibre-reinforced Duran glass composites (differing in the specific sol-gel supported production processes). Their dependence on the production pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
1
2
0
2
Order By: Relevance
“…However, a transition layer is also observed in SiC f -YMAS composites. A similar transition layer has also been found in SiC f -LAS Ponthieu et al, 1994) and in SiC f -Duran composites (Lewis et al, 1993;Hähnel et al, 1994). The present study has shown that the transition layer is a diffusion zone for matrix elements except yttrium in SiC f -YMAS composites.…”
Section: Edx Analyses Of Interfacial Regionsupporting
confidence: 90%
“…However, a transition layer is also observed in SiC f -YMAS composites. A similar transition layer has also been found in SiC f -LAS Ponthieu et al, 1994) and in SiC f -Duran composites (Lewis et al, 1993;Hähnel et al, 1994). The present study has shown that the transition layer is a diffusion zone for matrix elements except yttrium in SiC f -YMAS composites.…”
Section: Edx Analyses Of Interfacial Regionsupporting
confidence: 90%
“…For SiC(Nicalon) fibres in Duran glass the dependences of layer formation as well as of morphology and microchemistry on the processing conditions, particularly on the temperature ranging from about 1100 to 1340 • C and on the duration of hot pressing of typically 5 min to 4 h (cf [3,4]) were studied in detail. On the basis of these investigations and respective thermodynamic treatments a model was developed which divides the different chemical reactions into three steps leading to carbon-rich interlayers [5].…”
Section: Introductionmentioning
confidence: 99%
“…For SiC (Nicalon)-fibre-reinforced Duran glasses the morphology of fibre/matrix interlayers, the generation of these reaction layers as a function of the processing parameters (mainly time and temperature of hot-pressing) and the effect of such layers on the mechanical composite properties have been investigated in detail (Hähnel, 1995;Hähnel et al, 1995;Pippel et al, 1995). The influence of glassy phases on the mechanical behaviour, possibly occurring inside the reaction layers, will be focused on in the discussion below.…”
Section: Resultsmentioning
confidence: 99%